ENVIRONMENTAL MANAGEMENT IN JOINT STREAMS REGULATION BY TWO HYDROELECTRIC COMPLEXES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Lowland river water power developments are usually built to solve complex tasks on the basis of the requirements of rational use of water resources. First of all, operating conditions of hydroelectric complex structures should provide safety and economic efficiency in their work. Besides, they are aimed to satisfy various demands of water consumers. It is particularly important that behaviour of hydroelectric complex structures should satisfy contemporary requirements of environmental security. The most important task here is to create favourable ecological conditions of life for people who live in settlements located in the zone of influence of two hydroelectric complexes located on different rivers. Here, to achieve environmental targets it is necessary to interlink modes of operation of these water storage control structures. There are two water power developments built in the Republic of Bashkortostan, Russia, in the middle flow of the Belaya River. Both of them have considerable impact on the formation of level mode and different consumers’ water supply. They are Umaguzinskiy and Nugushskiy water power developments. Both hydroelectric complexes and their water reservoirs together satisfy the following generally accepted requirements of water consumers: - they prevent the lowering of the water level in the river Belaya (during low streamflow period) below the minimum values required to ensure proper water supply for industrial enterprises; - they generate electric power and provide industries and cities with electricity. To do that each water-economic complex has its own water reservoir and a set of retaining structures and required culvert installations.In addition, the following environmental requirements are imposed on co-regulation of water runoff: - protection of waterfronts of the towns Meleuz, Salavat, Ishimbay and Sterlitamak from flooding in flood season; -protection of the territories of refineries in flood season (during water rise). Umaguzinskiy water power development has the following water sluices to control water stream: 1) submerged flood-discharge outlet; 2) shore flood spillway; 3) aggregates of powerhouse. General water carrying capacity of hydroelectric complex structures is 3915 м3/c. Nugushskiy hydroelectric complex consists of hydraulic engineering structure power room (1) and left shore spillway (2). Combined water carrying capacity of all hydroelectric complex structures here is 1250 м3/c.The authors investigated operation modes of Nugushskiy and Umaguzinskiy water power developments when linked into one water-economic complex and came to the conclusion that modes of operation of these water storage control structures should be adjusted in accordance with the operational condition of the main pressure installations and of downstream flood-control facilities. In particular, it is necessary to take into account the unfinished state of flood prevention measures in the middle reaches of the river Belaya.